Antibiotic treatment in infants: effect on the gastro-intestinal microbiome and long term consequences - Linde Peeters; Siel Daelemans; Yvan Vandenplas (Indonesian Nutrition Association, 2018)
The gastrointestinal microbiome is crucial for the development of a balanced immune system. Antibiotics are frequently administered to infants and cause intestinal dysbiosis. This narrative review highlights the long term health consequences of antibiotic administration to infants and young children. The necessity of administration of antibiotics should be well considered, since an association with short term consequences such as antibiotic associated diarrhoea and long term adverse effects such as overweight, inflammatory bowel syndrome, allergic disease have been reported. Conclusion: The pros and cons of antibiotic administration to infants and young children should be considered.